(untitled) (European Journal of Pure and Applied Mathematics, 2011)
In this paper, two quite new theorems on degree of approximation of conjugate of functionsÂ Â fLip Î± class and fW(Lr,Î¾(t) class using (E,1)(C,1) product summability means of conjugate series of Fourier series have been established.